The magnitude of the germinal center B cell and T follicular helper cell response predicts long-lasting antibody titers to plague vaccination - Galloway, Darrell R.; Nguyen, Nguyen X.; Li, Jiahui; Houston, Nicholas; Gregersen, Gage; Williamson, E. Diane; Falkenberg, Frank W.; Herron, James N.; Hale, J. Scott (Frontiers in Immunology, 2022)
The development of a safe and effective vaccine against Yersinia pestis, the causative organism for plague disease, remains an important global health priority. Studies have demonstrated effective immune-based protection against plague challenge that is induced by plague antigen subunit vaccination in an aqueous alhydrogel formulation; however, whether these candidate vaccines in this formulation and presentation, induce long-lasting immunological memory in the form of durable cellular and antibody recall responses has not been fully demonstrated. In this study, we analyzed germinal center T follicular helper and germinal center B cell responses following F1V and F1 + V plague subunit immunization of mice with vaccines formulated in various adjuvants. Our data demonstrate that recombinant plague protein immunization formulated with IL-2/GM-CSF cytokines bound to alhydrogel adjuvant drive an increase in the magnitude of the germinal center T follicular helper and germinal center B cell responses following primary immunization, compared to vaccines formulated with Alhydrogel adjuvant alone. In contrast, plague protein subunit immunization combined with CpG ODN bound to alhydrogel increased the magnitude and duration of the germinal center Tfh and B cell responses following booster immunization. Importantly, enhanced germinal center Tfh and B cell responses correlated with long-lasting and high F1V-specific antibody titers and more robust antibody recall responses to F1V re-exposure. These findings indicate that vaccine formulations that drive enhancement of the germinal center Tfh and B cell responses are critical for inducing durable plague-specific humoral immunity.